Memoan ciceroi gen. et sp. nov., a remarkable new firefly genus and species from the Atlantic Rainforest (Coleoptera: Lampyridae) - Da Silveira, Luiz Felipe Lima; Mermudes, José Ricardo M. (Zootaxa, 2013)
A species of firefly discovered in a fragile and rapidly disappearing Atlantic Rainforest biome in Brazil does not fit into any of the existing subfamilies nor described generic categories in the Lampyridae and is described here as Memoan ci-ceroi gen. et sp. nov. and classed as Lampyridae Incertae sedis, as it exhibits features of both the Amydetinae and Lampy-rinae. An overview of subfamily arrangements and relevant generic characters is given to support this action. Memoan gen. nov. can be distinguished by its alveolate pronotum and elytra; subserrate antennae, antenommeres II–IX com-pressed, antennal sockets obliquely inserted on tubercles; labial palp one-segmented and obconic, and by its conspicuous pleuroventral suture.